Integrating Network Pharmacology and Molecular Docking to Identify the Active Substances and Mechanisms of Chrysanthemum Against Dry Eye (Global Journal of Medical Research, 2024)
Abstract not found
Keywords: chrysanthemum; dry eye; chinese medicine; network pharmacology; molecular docking